Ta-W-Ti alloy used in liquid metal corrosion environment and preparation method of Ta-W-Ti alloy ingot
By adding W and Ti elements to the tantalum alloy and using suspension smelting and vacuum carburizing processes, Ta-W-Ti alloy was prepared, which solved the problems of insufficient strength and poor corrosion resistance at high temperatures, and achieved liquid state Preparation of high-performance materials in metal corrosion environments, suitable for applications in complex working conditions.
Patent Information
- Application Number
- CN202411429193.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-14
- Publication Date
- 2025-01-03
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
Existing tantalum alloys are insufficient in strength at high temperatures and are difficult to meet the requirements of resistant to molten metals under long-term service conditions. Graphite materials are fragile and easy to corrode when used directly, making it difficult to meet the application requirements under complex operating conditions.
By adding W and Ti elements to the Ta matrix, the strength and carburizing properties of the alloy are improved, and Ta-W-Ti alloys are formed, and a tantalum tungsten titanium alloy ingot with excellent performance is prepared through suspension smelting and vacuum carburizing processes. Control the alloy composition and process parameters to ensure high temperature performance and corrosion resistance.
It has achieved high temperature strength and corrosion resistance improvement in liquid metal corrosion environments, provided new structural materials suitable for extreme environments, with wide application prospects, and improved the overall performance of the alloy by reducing impurities and oxygen content.
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of refractory metal material preparation, and in particular relates to a Ta-W-Ti alloy for use in a liquid metal corrosion environment and a method for preparing an ingot thereof. Background Art
[0002] Tantalum (Ta) has very good wear resistance, extremely excellent welding performance, excellent room temperature forming performance and outstanding high temperature mechanical properties, and its ductile-brittle transition temperature is relatively low. Tantalum and tantalum alloys have been widely used in the field of molten metals in the nuclear industry. Metals such as cerium and uranium are very active in chemical properties and easily react with metal crucible materials. The corrosion rate will be significantly accelerated at high temperatures, which puts strict requirements on the high temperature mechanical properties of the metal materials used and the ability to resist molten metal corrosion. In addition, it is also necessary to consider that in actual applications, devices may face various processing and forming requirements such as extrusion and bending, so the material must have a certain degree of room temperature plasticity.
[0003] However, it is worth noting that pure tantalum (Ta) has low strength and cannot meet the requirements for high-temperature strength under such extremely complex working conditions. It is also difficult to meet the actual needs for resistance to molten metal corrosion under long-term service conditions.
[0004] Graphite materials have thermal properties such as high temperature resistance, high thermal conductivity, low linear expansion coefficient, and excellent thermal shock resistance. They are also low-cost, not easily wetted by molten metals and slags, and have excellent chemical stability. They have been widely used in smelting metals and high-temperature alloys, and are commonly used as crucible and mold materials. However, graphite materials are brittle and not suitable for direct use, and metals are easily corroded. Therefore, tantalum alloys can improve their resistance to molten metal corrosion through surface carburizing, but the carburizing rate is slow. Based on this, there is an urgent need to develop new, high-performance tantalum alloys to better adapt to various complex application scenarios and needs. Summary of the invention
[0005] The technical problem to be solved by the present invention is to provide a Ta-W-Ti alloy for use in a liquid metal corrosive environment in view of the deficiencies of the above-mentioned prior art. The alloy improves the strength of the alloy by adding W element to the Ta matrix, and effectively improves the carburizing performance of the alloy by adding Ti. At the same time, Ti can also play a role in solid solution and precipitation strengthening to further improve the strength of the alloy, and surface carburization also improves the molten metal corrosion resistance, thereby obtaining a Ta-W-Ti alloy for use in a liquid metal corrosive environment.
[0006] In order to solve the above technical problems, the technical solution adopted by the present invention is: a Ta-W-Ti alloy for use in a liquid metal corrosion environment, characterized in that the alloy is composed of the following elements in percentage by mass: W 4%~6%, Ti 5%~30%, O≤0.022%, and the remainder is Ta and unavoidable impurities, and the alloy surface has a carburized layer.
[0007] In the present invention, the composition of the Ta-W-Ti alloy is controlled, wherein W and Ta are completely miscible, and are ideal solid solution strengthening elements in tantalum alloys. Adding a small amount of W element to pure Ta can improve the high temperature strength and thermal stability of tantalum alloys, and reduce sensitivity to temperature and strain rate. However, adding W to Ta to form a substitutional solid solution will cause the lattice around it to shrink, and the average lattice constant will decrease, causing the lattice gap in the crystal structure to change. This will reduce the solubility of C atoms in tantalum alloys on the one hand, and on the other hand, it will greatly increase the activation energy required for C atoms to diffuse into Ta. Therefore, the presence of W in the Ta matrix will hinder the diffusion of C atoms and increase the difficulty of carburizing. Therefore, the W content is set to 4%~6%; In addition, carburizing the surface of tantalum alloy can significantly reduce the corrosion rate of tantalum alloy in molten metal, but tantalum-tungsten alloy carburizes more slowly. The ability of alloying elements to form carbides is arranged from strong to weak as follows: Ti, Zr, V, Ta, Nb, W. Ti is currently the strongest carbide-forming element. Adding Ti helps to improve the carburizing ability of the alloy. On the other hand, the atomic radius of Ti is larger than that of Ta atoms. The addition of Ti elements increases lattice stress and increases structural defects. This increases the channels of carbon atoms during carburizing to a certain extent, improves the carburizing ability of tantalum alloys, and also improves the strength of tantalum alloys. However, excessive Ti will precipitate from the Ta matrix to form β-Ti and severely coarsen, which is not conducive to the thermal shock resistance of the alloy. Therefore, the Ti content is set to 5%~30%; In addition, the O content is generally the highest among all gaseous impurity elements in tantalum alloys. However, O in tantalum alloys is not conducive to the high temperature performance and molten metal corrosion resistance of tantalum alloys. Therefore, the O content in tantalum alloys is minimized to less than 0.022%.
[0008] The above-mentioned Ta-W-Ti alloy for use in a liquid metal corrosive environment is characterized in that the thickness of the carburized layer is not less than 25 μm. The present invention improves the carburizing performance of the tantalum alloy, controls the thickness of the carburized layer, and improves the molten metal corrosion resistance of the Ta-W-Ti alloy, and is suitable for use in a liquid metal corrosive environment.
[0009] In addition, the present invention also discloses a method for preparing a Ta-W-Ti alloy ingot in a liquid metal corrosive environment, characterized in that the method comprises the following steps: Step 1, uniformly mixing tantalum particles or tantalum blocks, tungsten particles or tungsten blocks and titanium sponge to obtain a mixture; Step 2: placing the mixture obtained in step 1 into a crucible of a vacuum suspension melting furnace, then evacuating the vacuum suspension melting furnace, then filling the furnace with argon gas, and then performing suspension melting for 3 to 6 times to obtain a tantalum-tungsten-titanium alloy primary ingot with uniform composition; Step 3, processing the tantalum-tungsten-titanium alloy primary ingot obtained in step 2 into chips using a lathe, and crushing it using a crusher to obtain alloyed chips; Step 4: gradually add the alloyed scraps in step 3 into the vacuum suspension melting furnace through a secondary feeder, and use an ingot pulling process to obtain a tantalum-tungsten-titanium alloy ingot; Step 5: subjecting the tantalum-tungsten-titanium alloy ingot obtained in step 4 to conventional forging, rolling and annealing to obtain a tantalum-tungsten-titanium alloy plate; Step 6: vacuum carburize the tantalum-tungsten-titanium alloy plate obtained in step 5 to obtain a Ta-W-Ti alloy for use in a liquid metal corrosion environment.
[0010] The present invention uses block or granular raw materials, adopts suspension smelting to prepare tantalum-tungsten-titanium alloy primary ingots, then mechanically processes them into alloyed debris, and then obtains tantalum-tungsten-titanium alloy ingots with uniform composition and excellent quality through a suspension smelting and ingot pulling process, and finally improves the molten metal corrosion resistance through carburizing to obtain Ta-W-Ti alloy for use in liquid metal corrosion environments. Conventional refractory alloy smelting uses powder raw materials with high impurity content. Although electron beam smelting and purification are subsequently used, it will cause a large amount of low-melting-point elements to volatilize. The present invention uses granular raw materials, which significantly reduces the content of impurity elements in the ingot. At the same time, a certain amount of argon is filled into the smelting process during suspension smelting to avoid a large amount of volatilization of the low-melting-point element titanium.
[0011] The above method is characterized in that the mass purity of the tantalum particles, tungsten particles and titanium sponge in step 1 is not less than 99.5%. The present invention controls the purity of the raw materials, thereby avoiding the introduction of a large amount of impurities from the source and ensuring the composition content of the alloy.
[0012] The above method is characterized in that the vacuuming in step 2 is to vacuumize to 6×10 -3 Pa, the gas pressure in the furnace is 20kPa~50kPa. The present invention controls the filling of a certain amount of high-purity argon gas, and the pressure value is much higher than the saturated vapor pressure of titanium, thereby avoiding the large-scale volatilization of titanium elements with low melting points, making the titanium recovery rate not less than 90%, and ensuring the uniformity of each element in the alloy.
[0013] The above method is characterized in that the speed of pulling the ingot in step 4 is 2 mm / min to 5 mm / min. The present invention improves the preparation efficiency while ensuring the surface quality of the ingot by controlling the speed of pulling the ingot.
[0014] The above method is characterized in that the room temperature tensile strength of the tantalum-tungsten-titanium alloy ingot in step 4 is not less than 690 MPa, the yield strength is not less than 590 MPa, and the elongation after fracture is not less than 15%.
[0015] Compared with the prior art, the present invention has the following advantages: 1. The present invention adds W and Ti elements to the Ta matrix to improve the high temperature performance of the alloy through solid solution strengthening and precipitation strengthening. At the same time, the addition of Ti element can effectively improve the carburizing performance of the tantalum alloy, and improve the corrosion resistance of molten metal through carburizing, so that the Ta-W-Ti alloy is suitable for working in extreme environments such as high temperature and molten metal, and is expected to be used as a new type of structural and corrosion-resistant material in the high temperature field, with broad application prospects.
[0016] 2. The present invention adopts suspension smelting to prepare alloy ingots. By adopting high-purity raw materials, the introduction of impurities is reduced. At the same time, a certain amount of argon (20kPa~50kPa) is filled in the smelting process, which effectively avoids the volatilization of Ti elements and reduces the oxygen content in the alloy. The problem that although the traditional electron beam smelting has a good impurity removal effect, its vacuum degree is generally lower than 0.01Pa, and the Ti element is in a free volatilization state during the smelting process, resulting in a large loss of Ti elements is solved. The problem that the traditional powder metallurgy is used to prepare Ta-W-Ti alloy, which avoids the burning of Ti elements, but the oxygen content in the alloy is generally greater than 0.2% is solved.
[0017] 3. The mass content of impurity oxygen in the Ta-W-Ti alloy of the present invention is less than 0.022%, the room temperature tensile strength is not less than 690 MPa, the yield strength is not less than 590 MPa, the elongation after fracture is not less than 15%, and the thickness of the carburized layer is not less than 25 μm, which has excellent performance.
[0018] 4. After conventional forging, rolling and annealing, the tantalum-tungsten-titanium alloy ingot prepared in the present invention has significantly improved strength and carburizing properties, and has good room temperature plasticity.
[0019] The technical solution of the present invention is further described in detail below through embodiments. DETAILED DESCRIPTION
[0020] Example 1 This embodiment includes the following steps: Step 1: Tantalum particles, tungsten particles and titanium sponge with a purity of not less than 99.5% are mixed evenly to obtain a mixture; the mixture is composed of the following elements in percentage by mass: W 4%, Ti 5%, and the remainder is Ta and unavoidable impurities; Step 2: Place the mixture obtained in step 1 into a crucible of a vacuum suspension melting furnace, and then evacuate the vacuum suspension melting furnace to 6×10 -3 Pa, then fill the furnace with argon gas to make the furnace pressure 50kPa, and then carry out three suspension smelting to obtain a tantalum-tungsten-titanium alloy primary ingot with uniform composition; Step 3, processing the tantalum-tungsten-titanium alloy primary ingot obtained in step 2 into chips using a lathe, and crushing it using a crusher to obtain alloyed chips; Step 4: gradually add the alloyed debris in step 3 into the vacuum suspension melting furnace through a secondary feeder, and simultaneously perform an ingot pulling process at an ingot pulling speed of 2 mm / min to obtain a tantalum-tungsten-titanium alloy ingot; Step 5: subjecting the tantalum-tungsten-titanium alloy ingot obtained in step 4 to conventional forging, rolling and annealing to obtain a tantalum-tungsten-titanium alloy plate; Step 6: Carry out vacuum carburization of the tantalum-tungsten-titanium alloy plate obtained in step 5 at 1500° C. for 10 hours to obtain a Ta-W-Ti alloy for use in a liquid metal corrosion environment.
[0021] After testing, the tantalum tungsten titanium alloy ingot prepared in this embodiment is composed of the following elements in percentage by mass: W 4.25%, Ti 4.51%, O 0.014%, the remainder is Ta and unavoidable impurities, and the titanium yield rate is 90.2%. The room temperature tensile strength of the alloy plate obtained by conventional forging, rolling and annealing of the tantalum tungsten titanium alloy ingot prepared in this embodiment is 692 MPa, the yield strength is 599 MPa, and the elongation after fracture is 23.75%. The thickness of the carburized layer in the Ta-W-Ti alloy prepared in this embodiment for use in a liquid metal corrosion environment is about 25 μm.
[0022] Comparative Example 1 In the comparative example, a commercial pure tantalum plate was used, with a room temperature tensile strength of 311 MPa, a yield strength of 232 MPa, and an elongation after fracture of 48.29%. It was vacuum carburized at 1500°C for 10 hours, and the thickness of the carburized layer was about 20 μm.
[0023] By comparing Example 1 and Comparative Example 1, it can be seen that the alloy plate prepared from the tantalum-tungsten-titanium alloy ingot in Example 1 has excellent room temperature tensile strength, yield strength and elongation after fracture compared with the pure tantalum plate, and compared with the pure tantalum plate under the same carburizing conditions, the obtained carburized layer is thicker and its resistance to molten metal corrosion is stronger.
[0024] Example 2 This embodiment includes the following steps: Step 1: Evenly mix bulk tantalum, bulk tungsten and sponge titanium with a purity of not less than 99.5% to obtain a mixture; the mixture is composed of the following elements in percentage by mass: W 6%, Ti 30%, and the remainder is Ta and unavoidable impurities; Step 2: Place the mixture obtained in step 1 into a crucible of a vacuum suspension melting furnace, and then evacuate the vacuum suspension melting furnace to 6×10 -3 Pa, then fill the furnace with argon gas to make the furnace pressure 20kPa, and then carry out 6 suspension smelting to obtain a tantalum-tungsten-titanium alloy primary ingot with uniform composition; Step 3, processing the tantalum-tungsten-titanium alloy primary ingot obtained in step 2 into chips using a lathe, and crushing it using a crusher to obtain alloyed chips; Step 4: gradually add the alloyed debris in step 3 into the vacuum suspension melting furnace through a secondary feeder, and simultaneously perform an ingot pulling process at an ingot pulling speed of 5 mm / min to obtain a tantalum-tungsten-titanium alloy ingot; Step 5: subjecting the tantalum-tungsten-titanium alloy ingot obtained in step 4 to conventional forging, rolling and annealing to obtain a tantalum-tungsten-titanium alloy plate; Step 6: Carry out vacuum carburization of the tantalum-tungsten-titanium alloy plate obtained in step 5 at 1500° C. for 10 hours to obtain a Ta-W-Ti alloy for use in a liquid metal corrosion environment.
[0025] After testing, the tantalum tungsten titanium alloy ingot prepared in this embodiment is composed of the following elements in percentage by mass: W 6.13%, Ti 29.1%, O 0.022%, the remainder is Ta and unavoidable impurities, and the titanium yield is 97%. The room temperature tensile strength of the alloy plate obtained by conventional forging, rolling and annealing of the tantalum tungsten titanium alloy ingot prepared in this embodiment is 954 MPa, the yield strength is 938 MPa, and the elongation after fracture is 16.94%. The thickness of the carburized layer in the Ta-W-Ti alloy prepared in this embodiment for use in a liquid metal corrosion environment is about 125 μm.
[0026] Example 3 This embodiment includes the following steps: Step 1: Tantalum particles, tungsten particles and titanium sponge with a purity of not less than 99.5% are mixed evenly to obtain a mixture; the mixture is composed of the following elements in percentage by mass: W 5%, Ti 10%, and the remainder is Ta and unavoidable impurities; Step 2: Place the mixture obtained in step 1 into a crucible of a vacuum suspension melting furnace, and then evacuate the vacuum suspension melting furnace to 6×10 -3 Pa, then fill the furnace with argon gas to make the furnace pressure 35kPa, and then carry out 4 times of suspension melting to obtain a tantalum-tungsten-titanium alloy primary ingot with uniform composition; Step 3, processing the tantalum-tungsten-titanium alloy primary ingot obtained in step 2 into chips using a lathe, and crushing it using a crusher to obtain alloyed chips; Step 4: gradually add the alloyed debris in step 3 into the vacuum suspension melting furnace through a secondary feeder, and simultaneously perform an ingot pulling process at an ingot pulling speed of 3 mm / min to obtain a tantalum-tungsten-titanium alloy ingot; Step 5: subjecting the tantalum-tungsten-titanium alloy ingot obtained in step 4 to conventional forging, rolling and annealing to obtain a tantalum-tungsten-titanium alloy plate; Step 6: Carry out vacuum carburization of the tantalum-tungsten-titanium alloy plate obtained in step 5 at 1500° C. for 10 hours to obtain a Ta-W-Ti alloy for use in a liquid metal corrosion environment.
[0027] After testing, the tantalum tungsten titanium alloy ingot prepared in this embodiment is composed of the following elements in percentage by mass: W 4.98%, Ti 9.83%, O 0.016%, the remainder is Ta and unavoidable impurities, and the titanium yield rate is 98%. The room temperature tensile strength of the alloy plate obtained by conventional forging, rolling and annealing of the tantalum tungsten titanium alloy ingot prepared in this embodiment is 723 MPa, the yield strength is 604 MPa, and the elongation after fracture is 21.44%. The thickness of the carburized layer in the Ta-W-Ti alloy prepared in this embodiment for use in a liquid metal corrosion environment is about 56 μm.
[0028] After testing, the high entropy alloy bar prepared in this embodiment has a good appearance, no obvious casting defects, uniform composition, and no shrinkage cavities.
[0029] The above is only a preferred embodiment of the present invention and does not limit the present invention in any way. Any simple modification, change and equivalent change made to the above embodiment according to the technical essence of the present invention still falls within the protection scope of the technical solution of the present invention.
Claims
1. A Ta-W-Ti alloy for use in liquid metal corrosive environments, characterized in that: The alloy is composed of the following elements in percentage by mass: W 4%-6%, Ti 5%-30%, O≤0.022%, and the remainder is Ta and inevitable impurities. The surface of the alloy has a carburized layer.
2. The Ta-W-Ti alloy for use in liquid metal corrosive environments according to claim 1, characterized in that: The thickness of the carburized layer is not less than 25 μm.
3. A method for preparing a Ta-W-Ti alloy ingot resistant to liquid metal corrosion as claimed in claim 1 or 2, characterized in that: The method comprises the following steps: Step 1, uniformly mixing tantalum particles or tantalum blocks, tungsten particles or tungsten blocks and titanium sponge to obtain a mixture; Step 2: placing the mixture obtained in step 1 into a crucible of a vacuum suspension melting furnace, then evacuating the vacuum suspension melting furnace, then filling the furnace with argon gas, and then performing suspension melting for 3 to 6 times to obtain a tantalum-tungsten-titanium alloy primary ingot with uniform composition; Step 3, processing the tantalum-tungsten-titanium alloy primary ingot obtained in step 2 into chips using a lathe, and crushing it using a crusher to obtain alloyed chips; Step 4: gradually add the alloyed scraps in step 3 into the vacuum suspension melting furnace through a secondary feeder, and use an ingot pulling process to obtain a tantalum-tungsten-titanium alloy ingot; Step 5: subjecting the tantalum-tungsten-titanium alloy ingot obtained in step 4 to conventional forging, rolling and annealing to obtain a tantalum-tungsten-titanium alloy plate; Step 6: vacuum carburize the tantalum-tungsten-titanium alloy plate obtained in step 5 to obtain a Ta-W-Ti alloy for use in a liquid metal corrosion environment.
4. The method according to claim 3, characterized in that The mass purity of the tantalum particles, tungsten particles and titanium sponge described in step 1 is not less than 99.5%.
5. The method according to claim 3, characterized in that: The vacuuming in step 2 is to vacuumize to 6×10 - 3 Pa, the gas pressure in the furnace is 20kPa~50kPa.
6. The method according to claim 3, characterized in that The pulling speed in step 4 is 2 mm / min~5 mm / min.
7. The method according to claim 3, characterized in that The room temperature tensile strength of the tantalum-tungsten-titanium alloy plate described in step five is not less than 690 MPa, the yield strength is not less than 590 MPa, and the elongation after fracture is not less than 15%.
